Chemical Composition and Quality Characteristics of Wheat Bread Supplemented with Leafy Vegetable Powders - T. V. Odunlade; A. A. Famuwagun; K. A. Taiwo; S. O. Gbadamosi; D. J. Oyedele; O. C. Adebooye (Journal of Food Quality)
The study investigated the effect of supplementation of the leaf powders of Telfairia occidentalis, Amaranthus viridis, and Solanum macrocarpon on the chemical composition and the quality characteristics of wheat bread. The bread samples were supplemented with each of the vegetable leaf powders at 1%, 2%, and 3% during preparation. The bread samples were assayed for proximate composition, mineral composition, physical, sensory, and antioxidant properties using standard methods. The addition of vegetable powders significantly increased the protein (9.50 to 13.93%), fibre (1.81 to 4.00%), ash (1.05 to 2.38%), and fat (1.27 to 2.00%). Supplementation with vegetable powder however significantly decreased (p<0.05) the carbohydrate and moisture contents. Significant (p<0.05) increases were recorded for all evaluated minerals as the level of vegetable powder increased. Supplementation with vegetable powder caused significant decrease in total phenolic content, percentage DPPH inhibition, metal chelating ability, ferric reducing antioxidant power, and total antioxidant capacity. Sensory results showed that there was significant decrease in sensory qualities with increasing supplementation. This therefore suggests that bread supplemented with vegetable powder could have more market penetration if awareness is highly created.